2015
DOI: 10.4049/jimmunol.1401182
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepaticaFatty Acid Binding Protein Inhibits TLR4 Activation and Suppresses the Inflammatory Cytokines Induced by Lipopolysaccharide In Vitro and In Vivo

Abstract: Toll-like receptor 4 (TLR4), the innate immunity receptor for bacterial endotoxins, plays a pivotal role in the induction of inflammatory responses. There is a need to develop molecules that block either activation through TLR4 or the downstream signaling pathways to inhibit the storm of inflammation typically elicited by bacterial lipopolysaccharide (LPS), which is a major cause of the high mortality associated with bacterial sepsis. We report here that a single intraperitoneal injection of 15μg Fasciola hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
78
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 88 publications
11
78
0
2
Order By: Relevance
“…7C,D). These results indicate that Fh15 down regulates the expression of inflammatory cytokines at similar intensity to that previously demonstrated by native Fh12 12 .
Figure 7Fh15 suppressed the expression of TNFα and IL1β cytokines from mouse BMDM and human monocyte cell line (THP1-Blue CD14) in response to LPS. Bone marrow derived macrophages (BMDM) from naive C57BL/6 mice and THP1-Blue CD14 cells were treated with 5 μg/ml or 10 μg/ml Fh15, respectively 30 min before stimulation with LPS (100ng/ml or 1 μg/ml, respectively).
…”
Section: Resultssupporting
confidence: 76%
“…7C,D). These results indicate that Fh15 down regulates the expression of inflammatory cytokines at similar intensity to that previously demonstrated by native Fh12 12 .
Figure 7Fh15 suppressed the expression of TNFα and IL1β cytokines from mouse BMDM and human monocyte cell line (THP1-Blue CD14) in response to LPS. Bone marrow derived macrophages (BMDM) from naive C57BL/6 mice and THP1-Blue CD14 cells were treated with 5 μg/ml or 10 μg/ml Fh15, respectively 30 min before stimulation with LPS (100ng/ml or 1 μg/ml, respectively).
…”
Section: Resultssupporting
confidence: 76%
“…Although helminth infection is associated with an increase in circulating LPS, there are numerous helminth-mediated immunoregulatory mechanisms in place to reduce LPS-associated inflammatory response. For example, helminths infections are beneficial in sepsis by inducing IL-10 expression (6), and Fasciola hepatica secretes fatty acid binding proteins to reduce inflammatory responses (8). Our data suggest hookworm infection also protects from sepsis through hRetn-dependent and hRetn-independent mechanisms.…”
Section: Discussionmentioning
confidence: 77%
“…Recent studies have shown that chronic infection with filarial nematode Litomosoides sigmodontis protects mice from fatal sepsis through TLR2-dependent activation of macrophages and inhibition of proinflammatory cytokines (6). In addition, helminth antigens such as Acanthocheilonema viteae ES-62 and Fasciola hepatica fatty acid binding protein bind to TLR4 and reduce proinflammatory cytokine production (7,8).…”
mentioning
confidence: 99%
“…Many studies show that tissue extracts or E/S products from helminths can suppress mammalian immune cell activation in vitro (29)(30)(31)(32) and ameliorate the severity of inflammatory disease in murine model systems (14,18,19,29,30,33,34). The demonstration herein that systemic administration of a crude extract of adult H. diminuta parasites dosedependently inhibits DSS-induced colitis adds to awareness of the ability of helminth-derived molecules to suppress intestinal inflammation (19,21,35).…”
Section: Discussionmentioning
confidence: 90%